EFFECT OF SEVERE HYPERHOMOCYSTEINEMIA SECONDARY TO PERNICIOUS ANEMIA IN YOUNG ACUTE CORONARY SYNDROME - SUMATHI.K.,; VIDHYA LOGINI.T.,; PRAKASH.M, (International Journal of Pharma and Bio Sciences, 2015)
Vitamin B12 deficiency which results in pernicious anemia1, 2, hyperhomocysteinemia, a known risk factor for venous and arterial thrombosis. We report on a 33-year-old man presented to the emergency room with complaints of vague chest discomfort and pain radiating from the shoulder on both sides to both the fore arms along the ulnar borders. and ECG showed transient J point ST elevation in V1- V4. He has been admitted in cardiac ICU for further management. Found to have Single vessel disease [Distal LAD].Laboratory evaluation revealed pernicious anemia and high serum homocysteine[>50 µmol/L ] . Treatment with subcutaneous vitamin B12 results in rapid sustained decline in homocysteine levels with no subsequent thrombotic events through 1 year of follow-up. This case demonstrates that pernicious anemia may cause significant cardiovascular complications due to hyperhomocysteinemia3,4,5, and should be considered in the diagnosis of a patient with a thrombotic event .